Zróżnicowanie przestrzenne działalności pozarolniczej i poziomu rozwoju ekonomicznego na obszarach wiejskich województwa kujawsko-pomorskiego = Spatial differentiation non-agricultural activity and economic development level of rural areas of kujawsko-pomorskie voivodship - Piotrowska, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Non-agricultural activity is the main economic development factor of socio-economic systems including rural areas. Characteristics, analysis, spatial differentiation of basic resources and non-agricultural activity have been presented. Moreover, an attempt was made to evaluate the economic development level of rural areas of the kujawsko-pomorskie voivodship with the use of 2 methods, among others evaluation of the gross value added. The highest development is characteristic for suburban rural areas situated in the neighbourhood of the biggest cities which are economically strong like Bydgoszcz and Torun.
Keywords: obszary wiejskie; działalność pozarolnicza; rozwój ekonomiczny; rural areas; non-agricultural activity; economic development